Kemampuan Membaca Siswa Dengan Menggunakan Metode SQ3R di Sekolah Dasar - Pratama, Diansyah; Hetilaniar, Hetilaniar; Dirgantara, Marvinda Rizki Dita (Indonesian Research Journal on Education, 2022)
This study aims to see and determine the effect of the SQ3R method on the reading ability of classstudents. The experimental method of this type of research is True-Experimental Design in theform of Posttest-Only Control Design. The research variable is the independent variable using the SQ3R method (X) and the dependent variable is reading ability (Y). The population of this study were all fourth grade students of SD Negeri 233 Palembang, totaling 49 students. Data collection techniques using tests and interviews. The instrument for measuring reading ability uses a posttest in the form of a multiple choice objective test. The validity of the test instrument was tested using the product moment correlation formula and to determine its reliability it was tested using the Kuder Richardson (KR) 21 formula. The data analysis technique used the t test, which previously had known normality and homogeneity. The posttest value of the experimental class was 81.43, the control class used the method of reading the posttest value of 73.33. The results of the t-test t-table 2.012 obtained tcount 2.296, there is a significant effect on the use of the SQ3R method on students' reading ability in determining the main idea of a paragraph.